GAMBARAN INFESTASI Ascaris lumbricoides DAN Trichuris trichiura PADA MURID KELAS I, II, DAN III SD NEGERI 45 DI LINGKUNGAN PEMBUATAN BATU BATA KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Muhammad Nasir; Lilly Haslinda; Enikarmila Asni (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Ascaris lumbricoides and Trichuris trichiura are part of Soil Transmitted Helminthes (STH) which need gristle soil for it’s egg development and maturation as well as media to be infective. The aim of this research was to describe the infestation of Ascaris lumbricoides and Trichuris trichiura on elementary students grade I, II, and III SDN 45 in brick made home industry Kecamatan Tenayan Raya Pekanbaru. This research was cross sectional descriptive study which was done in August 2013. From 83 samples, 20 students (24%) are infested with Ascaris lumbricoides, 17 students (20.4%) are infested with Trichuris trichiura and 6 students (7.2%) are having mix infestation. Infected students have poor washing hand habits in their house 25 students (30.1%), 34 students (40.9%) have poor washing hand habits before eat junkfood. Meanwhile infected students have good cutting nail habits 30 students (36.1%) and good defecating habits 29 students (34.9%). These results indicate that the STH infestation influenced not only one habit but also influenced by other habits.Keywords: Ascaris lumbricoides infestation, Trichuris trichiura; washing hand; cutting nail; defecation.